Pendekatan Bahasa dalam Dakwah oleh Ustadzah Oki Setiana Dewi - Dea Wasilatul Amal; Tauhid Zidan Alifkan (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This article explores the communication language employed by Ustadzah Oki Setiana Dewi in her preaching activities. The aim of this study is to examine the effectiveness of the language in enhancing audience understanding and acceptance of preaching messages. The methodology involves a literature review with qualitative analysis of Ustadzah Oki’s sermons available on digital platforms. The findings reveal that Ustadzah Oki’s communication style is characterized by simplicity, friendliness, and empathy. These traits enable her preaching to be well-received by diverse groups, particularly the younger generation. Furthermore, Ustadzah Oki often uses inspiring stories and analogies closely related to everyday life, making it easier for the audience to grasp the messages. Her soft tone and choice of positive words also create a comforting and engaging atmosphere. This approach not only effectively conveys the message but also builds emotional connections with the audience. The study also highlights positive feedback from audiences, evident from various comments and responses on social media. Many feel motivated and inspired by her inclusive preaching style, which transcends social, age, and educational backgrounds. This article suggests that similar approaches should be widely adopted in preaching to ensure that religious messages are universally accessible. In conclusion, Ustadzah Oki’s friendly, simple, and empathetic communication approach significantly enhances the effectiveness of her preaching and strengthens emotional bonds with her audience. This model of communication is relevant in modern preaching contexts and serves as an inspiration for other preachers to integrate universal Islamic values with creative and heartfelt communication methods. Thus, preaching becomes not only a medium for conveying religious teachings but also a tool for fostering broader social harmony.